Using the five-factor model of personality to identify an optimal SWAT team member - Sjöberg, Anders (International journal of police science & management, 2025)
This study, based on the five-factor model (FFM) of personality, aimed to identify personality traits associated with the most optimal special weapons and tactics (SWAT) team member. SWAT teams are tasked with pre-empting and responding to terrorist threats, conducting hostage rescue operations, and managing situations that exceed the capabilities of conventional law enforcement agencies. The study sought to provide a deeper understanding of how personality traits function within the high-stakes context of these teams. It involved 159 male SWAT officers in active service within the Swedish Police Authority. A work analysis instrument, the Personality Job Profiler (PJP), was administered to these officers, who served as subject matter experts (SMEs) in a comprehensive personality work analysis. Specifically, the study addressed two research questions: How can an optimal SWAT police officer personality profile be operationalized when translated to the FFM of personality? What is the association between this optimal SWAT profile and the ratings of ten Diagnostic and Statistical Manual of Mental Disorders personality disorder profiles, based on the FFM of personality? The findings suggest that successful SWAT officers should exhibit low neuroticism and high conscientiousness, specifically featuring low vulnerability and high levels of competence, dutifulness, and self-discipline. Notably, the SWAT profile differs significantly from personality disorders, such as borderline, schizotypal, dependent, and avoidant, when operationalized with the FFM of personality. These results have significant implications for developing predictors for the selection process and can enhance the selection procedures for future SWAT members. This may also prompt further studies on criteria-related validity using various personality assessment methods.